Synthesis of Mexican Symphypleona (Hexapoda: Collembola): updated checklist with ecological and geographical distribution - Magaña-Martínez, César S.; Palacios-Vargas, José G.; Navarrete-Heredia, José L. (Zootaxa, 2019)
A taxonomic list of recorded Symphypleona from Mexico is presented. Data also includes a nomenclatorial update, distribution per political entity and habitat preferences. It is indicated that 28 genera and 73 species are currently distributed in 23 of the 32 states of Mexico. Quintana Roo represents the most diverse state (27 species) followed by Jalisco and Hidalgo (20 spp.). Reviews consulted indicate that eleven endemic species have been recorded so far from Mexico. According to the literature, one-third of the collected specimens across Mexico from leaf litter have yielded Symphypleona. The three most diverse genera recorded are, Sminthurides with 9 species, Sminthurinus and Sminthurus with 7 species each.